Hoptopia : A World of Agriculture and Beer in Oregon's Willamette Valley - Kopp, Peter Adam (Book collections on Project MUSE., 2016)
"Hoptopia argues that the current revolution in craft beer is the product of a complex global history that converged in the hop fields of Oregon's Willamette Valley. What spawned from an ideal environment and the ability of regional farmers to grow the crop rapidly transformed into something far greater because Oregon farmers depended on the importation of rootstock, knowledge, technology, and goods not only from Europe and the Eastern United States but also from Asia, Latin America, and Australasia. They also relied upon a seasonal labor supply of people from all of these areas as a supplement to local Euroamerican and indigenous communities to harvest their crops. In turn, Oregon hop farmers reciprocated in exchanges of plants and ideas with growers and scientists around the world, and, of course, sent their cured hops into the global marketplace. These global exchanges occurred not only during Oregon's golden era of hop growing in the late nineteenth and early twentieth centuries, but through to the present in the midst of the craft beer revival. The title of this book, Hoptopia, is a nod to Portland's title of Beervana and the Willamette Valley's claim as an agricultural Eden from the mid-nineteenth century onward. But the story is fundamentally about how seemingly niche agricultural regions do not exist and have never existed independently of the flow of people, ideas, goods, and biology from other parts of the world. To define Hoptopia is to define the Willamette Valley's hop and beer industries as the culmination of all of this local and global history. With the hop itself as a central character, this book aims to connect twenty-first century consumers to agricultural lands and histories that have been forgotten in an era of industrial food production"--Provided by publisher.